The development of immunosorbents for the treatment of systemic lupus erythematosus via hemoperfusion - Yu, Yameng; Ou, Lailiang (Frontiers in Medicine, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune disease (AID) that involves multiple organ systems and is characterized by elevated levels of autoantibodies (ANA) and immune complexes. The immunoadsorption technique uses an extracorporeal clearance process to remove pathogenic toxins from patients' blood and alleviate disease symptoms. An immunosorbent is a key component of the immunoadsorption system that determines therapeutic efficacy and safety. Immunosorbents are prepared by immobilizing antibodies, antigens, or ligands with specific physicochemical affinities on a supporting matrix. Immunosorbents and pathogenic toxins bind via affinity adsorption, which involves electrostatic interactions, hydrogen bonds, hydrophobic interactions, and van der Waals forces. Immunosorbents are classified on the basis of their interaction mechanism with toxins into three categories: non-selective, semi-selective, and highly selective. This review aimed to summarize the current status of various commercial immunosorbents that are used to treat SLE. Moreover, recent developments in immunosorbents have heightened the need for a brief discussion about specific ligands and a supporting matrix.